2022
DOI: 10.1108/compel-06-2021-0185
|View full text |Cite
|
Sign up to set email alerts
|

Cascade controllers design based on model matching in frequency domain for stable and integrating processes with time delay

Abstract: Purpose This paper aims to present an efficient and simplified proportional-integral/proportional-integral and derivative controller design method for the higher-order stable and integrating processes with time delay in the cascade control structure (CCS). Design/methodology/approach Two approaches based on model matching in the frequency domain have been proposed for tuning the controllers of the CCS. The first approach is based on achieving the desired load disturbance rejection performance, whereas the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…A series plant, G p1 (s) = e À0:7s =s 2 and G p2 (s) = e À0:3s =(s + 1) was studied by C xakırog˘lu et al 14 and Siddiqui et al 16 In C xakırog˘lu et al, 14 the output decomposition method is presented with two outer-loop controllers, G c1a (s) = 0:833 and G c1b (s) = 0:333, and inner controller as G c2 (s) = 3:33s + 1=s. Whereas in Siddiqui et al, 16 G c2 = 3:74 + 7:95=s and G c1 = 0:16 + 0:02=s + 0:56s were suggested. After adopting the proposed controller, l = 1:28 and b = 1:02 are obtained from the chosen g m = 2:5 and f m = 52:288.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A series plant, G p1 (s) = e À0:7s =s 2 and G p2 (s) = e À0:3s =(s + 1) was studied by C xakırog˘lu et al 14 and Siddiqui et al 16 In C xakırog˘lu et al, 14 the output decomposition method is presented with two outer-loop controllers, G c1a (s) = 0:833 and G c1b (s) = 0:333, and inner controller as G c2 (s) = 3:33s + 1=s. Whereas in Siddiqui et al, 16 G c2 = 3:74 + 7:95=s and G c1 = 0:16 + 0:02=s + 0:56s were suggested. After adopting the proposed controller, l = 1:28 and b = 1:02 are obtained from the chosen g m = 2:5 and f m = 52:288.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…One can see From Figure 17, it can be inferred that the maximum permitted perturbation is 70% because any additional rise in perturbation causes output from the system to become excessively oscillatory. When we tested the methods under the measurement noise with variance = 0.001, Siddiqui et al's 16 method obtained large variations in a control signal. The noise test also proved the proposed scheme's robustness as per Figures 18 and 19.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 3 more Smart Citations